Experimental transmission of Sparicotyle chrysophrii (Monogenea: Polyopisthocotylea) to gilthead seabream (Sparus aurata) and histopathology of the infection - Sitjà-Bobadilla, Ariadna; Alvarez-Pellitero, Pilar (Folia parasitologica, 2009)
The polyopisthocotylean Sparicotyle chrysophrii (Van Beneden et Hesse, 1863) was experimentally transmitted to gilthead seabream (Sparus aurata L.) by exposure to eggs (EGT) and by cohabitation with naturally parasitized fish (CT). In EGT trials, the infection was successfully transmitted by introducing containers with monogenean eggs in the fish tanks, with the highest infection level (85.7% prevalence, 3.3 mean intensity) achieved at 6 weeks post exposure (p.e.) to the infection dose of 650 eggs per tank. In CT trials, the progression of the infection was faster and reached higher levels than in EGT. When using small fish juveniles (30 g) (CT-2), infection reached 100% prevalence (mean intensity 8 monogeneans/fish) at 5 weeks p.e., but no eggs could be found in the fish even 10 weeks p.e. By contrast, when larger juveniles (150 g) were used (CT-1), infection levels were lower, but mature adults with eggs were detected starting from 8 weeks p.e. The effect of the parasite on the condition factor, haematocrit, haemoglobin concentration (Hb), red blood cell counts, mean corpuscular haemoglobin concentration (MCHC), mean corpuscular haemoglobin content (MCH) and mean cellular volume (MCV) of infected fish was studied in CT trials. The infection produced hypochromic anaemia, since Hb concentration significantly decreased at 5 and 10 weeks p.e. in CT-2 and at 8 weeks p.e. in CT-1. MCHC was significantly lower in parasitized than in control fish at 5 and 8 weeks p.e. in CT-2 and CT-1, respectively. Also in CT-1, MCH was lower and circulating immature erythrocytes, granulocytes and plasma cells were higher in infected fish than in control ones at 8 weeks p.e. The histopathological effects of the monogenean on the gills of naturally infected fish consisted of lamellar shortening, clubbing and synechiae. The proliferation of the epithelial tissue produced fusion of secondary lamellae, and abundant chloride cells were observed.
Keywords: Animals; protozoální infekce zvířat; nemoci ryb; Sea Bream; zvířata; Host-Parasite Interactions; Fish Diseases; mořan zlatý; interakce hostitele a parazita; Protozoan Infections, Animal; Eukaryota